Application of water repellent concrete infrastructure / Muhamad Hafizan Mat Fauzi - Mat Fauzi, Muhamad Hafizan (2017)
Flood affected the strength of structure and infrastructure of the building. It is due to that concrete is a porous material which water can easily penetrate into the concrete causing the decrement of durability of the concrete. It is a need to improve concrete to repel water. The modified silanes/siloxanes (SP50) react as protective agent is needed for water repellent for concrete added to fresh concrete during its production process as an integral water repellent. The aim of this study is to determine the physical performance of the concrete mix with the SP50 as a water repellent agent. SP50 is added to other concrete mixed until a homogenous formulation is obtained. The physical properties of SP50 are in white powder and inorganic. The concrete cube were prepared by using 100mm X 100mm X 100mm dimension and about 32 cubes prepared for the physical test. Visual test, capillary test, rebound hammer test, Ultrasonic Pulse velocity (UPV) test, cube compression test and water penetration test have been carried out. In this study, the result for visual test is not available for SP50 mixed. A better capillary test result shown in SP50 mixed than the control samples. The rate of water absorption in control samples were higher compared with the SP50 mix which is 1.36% and 0.67% respectively. For rebound hammer test, the results show that the compressive strength for SP50 mixed is higher compared with the control samples. The result of SP50 mixed are 30.33 N/mm2 and 30 N/mm2 for the control samples. There is no reduction in strength for the SP50 mixed concrete cube. In UPV test, average velocity for the SP50 mix is higher with the control samples which is 3.83 Km/s and 3.79 Km/s respectively. SP50 mixed were categorized as good grading concrete and it had been observed that UPV is not influent by the SP50 mixed samples. For the destructive test of cube compression and water penetration, both of the result produced a better result compared with the control samples. The average strength for the 28th day for SP50 mixed and control samples are 34.82 N/mm2 and 33.97 N/mm2 respectively. The percentage of concrete strength between SP50 mixed and control samples is 16.07% and 13.23% respectively higher from the target concrete strength which is 30 N/mm2. It had been observed that the result of SP50 mixed did not affected the concrete strength of the cube. Water penetration result in SP50 mixed is lower compared with the control samples which is 3.5 cm and 4.5 cm respectively. SP50 mixed improved the ability of concrete to repel water. This can be concluded that SP50 mixed is suitable for water repellent for concrete.